Structure and Composition of Prey Communities Associated with Malaysian Mahseer, Tor tambra Diet Based on DNA Metabarcoding: Implication for Conservation - Nur Farhana Mohd Yusoff; Shukor Md Nor; Shairah Abdul Razak (Tropical Life Sciences Research, 2025)
Quantifying dietary composition is crucial for basic ecological research and to formulate conservation management. For predatory fishes, DNA-metabarcoding can yield more accurate estimates than conventional morphological-based analyses. In Southeast Asia, Malaysian mahseers are experiencing declines in the wild due to their commercial and aesthetic value. Current practice in artificial propagation for mahseer has yet to fulfil high market demand due to constraints in dietary formulations that affect fish fertility and optimal growth. Here we applied cytochrome oxidase I (COI) metabarcoding with one species of Malaysian mahseer, Tor tambra or ‘kelah’, to characterise their food assimilation and feeding habits from seven different locations of wild and farm origins. Prey DNA sequences were grouped into 54 taxonomic groups at the species level.The diet comprised four predominant classes: Insecta, Actinopterygii, Arachnida and Aconoidasida. Representative taxa from each class were detected in wild and farmed fish. However, less than a quarter of the total taxa overlapped between both fish origins. Non-metric multidimensional scaling (NMDS) indicated greater prey taxonomic diversity and composition in wild fish across different rivers compared to those in farmed fish (PERMANOVA, pseudo-F = 1.959, p < 0.05). Our findings suggest that prey availability from the surrounding play roles in determining the fish food composition and dietary overlap. Expanding dietary analyses could offer ways to optimise diet for cultured fish as one of strategies to reduce fishing pressure on wild populations.